PENGARUH KINERJA KEUNGAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL PEMODERASI - Abdul Gaffar Rafid; Hotman Tohir Pohan; Ice Nasyrah Noor (Jurnal Akuntansi Trisakti, 2017)
The Study examined the effect of the allocation of the cost of social responsibility as a proxy of the disclosure of Corporate Social Responsibility) on the relationship between ROA as a proxy of the financial performance of the company’s value and the impact of the cost allocation of social responsibility as a proxy of the financial performance of the company’s value. The purpose of research is to find empirical evidence of (a) the effect of financial performance ROA on firm value, (b) the effect of the financial performance of CR on firm value (c) the effect of CSR on the relationship between ROA enterprise value (d) the effect of CSR on the relationship between CR with the value of the company.The sample in this research is manufacturing companies listed in Indonesia Stock Exchange (IDX) in the range of 2013-2015. Samples were as many 33 companies with 95 observation. Analysis of data using multiple linear regression analysis.Result of research by linear regression analysis showed that the ROA have negative significant effect on firm value. Than the results of linear regression analysis showed that the CR also has a negative significant effect on firm value. Furtermore, linear regression analysis reveals that the disclosure of CSR is not able to oderate the relationship between ROA on firm value. But unlike the CR, research results show that the disclosure of CSR is able to moderate the relationship between CR on firm value. Simulataneous the independent variable affects the company’s value.